Selective Liver Estrogen Receptor α Modulation Prevents Steatosis, Diabetes, and Obesity Through the Anorectic Growth Differentiation Factor 15 Hepatokine in Mice. Issue 7 (29th April 2019) - Guillaume, Maeva; Riant, Elodie; Fabre, Aurélie; Raymond‐Letron, Isabelle; Buscato, Melissa; Davezac, Morgane; Tramunt, Blandine; Montagner, Alexandra; Smati, Sarra; Zahreddine, Rana; Palierne, Gaëlle; Valera, Marie‐Cécile; et al.
Abstract : Hepatocyte estrogen receptor α (ERα) was recently recognized as a relevant molecular target for nonalcoholic fatty liver disease (NAFLD) prevention. The present study defined to what extent hepatocyte ERα could be involved in preserving metabolic homeostasis in response to a full (17β‐estradiol [E2]) or selective (selective estrogen receptor modulator [SERM]) activation. Ovariectomized mice harboring a hepatocyte‐specific ERα deletion ( LERKO mice) and their wild‐type (WT) littermates were fed a high‐fat diet (HFD) and concomitantly treated with E2, tamoxifen (TAM; the most used SERM), or vehicle. As expected, both E2 and TAM prevented all HFD‐induced metabolic disorders in WT mice, and their protective effects against steatosis were abolished in LERKO mice. However, while E2 still prevented obesity and glucose intolerance in LERKO mice, hepatocyte ERα deletion also abrogated TAM‐mediated control of food intake as well as its beneficial actions on adiposity, insulin sensitivity, and glucose homeostasis, suggesting a whole‐body protective role for liver‐derived circulating factors. Moreover, unlike E2, TAM induced a rise in plasma concentration of the anorectic hepatokine growth differentiation factor 15 (Gdf15) through a transcriptional mechanism dependent on hepatocyte ERα activation. Accordingly, ERα was associated with specific binding sites in the Gdf15 regulatory region in hepatocytes from TAM‐treated mice but not under E2 treatment due to specific epigenetic modifications. Finally, all the protective effects of TAM were abolished in HFD‐fed GDF15‐ knockout mice. Conclusion: We identified the selective modulation of hepatocyte ERα as a pharmacologic strategy to induce sufficient anorectic hepatokine Gdf15 to prevent experimental obesity, type 2 diabetes, and NAFLD.